POLA KEMITRAAN ANTARA PEMERINTAH, PIHAK SWASTA DANMASYARAKAT DALAM PENGEMBANGAN SEKTOR PERKEBUNANKELAPA SAWIT:STUDI DINAS PERKEBUNAN PROVINSI KALIMANTAN TENGAH - Agustina (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2016)
This study aims to explain, describe and analyze patterns of partnership between government, the private sector and civil society in the development of oil palm plantations as well as factors inhibiting and supporting factors. The research method using descriptive qualitative research. Data analysis technique is done through data reduction, data presentation and verification. The results showed that a partnership with a core pattern of plasma and partnership schemes MSA (Management One-Stop), KKPA (Primary Cooperatives Members), IGA (Income Generating Activity).There is a limiting factor and driving force in the partnership. Obstacle factor is lack of knowlegde about partnership and obligations in the course of partnerships at every actor partnership, conflict, limited land, in-consistency of each actor in the partnership, the decline in palm oil prices. The push factor is the regulatory and price.